Associations between HIV, TB and psychological distress among a sub-sample of a nationally representative study of South African adults: a secondary data analysis - de Wit, Marizanne (Department of Psychiatry and Mental Health, 2023)
Introduction: South Africa faces an immense burden of disease, considering that it is the epicentre of the global HIV and TB pandemics. Moreover, the burden of mental ill-health is a growing concern due to its prominent association with infectious diseases. While global research evidence hasshed some light on the effects of psychological distress on communicable diseases such as HIV and TB and vice versa, including the effects of distress on medication adherence, the association between psychological distress and HIV and TB co-morbidity among South African adults remains elusive. Aims: This study aims to determine the prevalence of psychological distress among South Africans adults, what socio-demographic factors are associated with psychological distress, whether HIV or comorbid TB and HIV is associated with psychological distress and finally, to investigate the association between depression and non-adherence among adults who live with HIV or those who have both HIV/TB. Methods: This study made use of cross-sectional data collected in 2017 as part of the fifth wave of nationally representative surveys from the South African National HIV Prevalence, Incidence, Behaviour and Communication Survey (SABSSM). Only participants between the ages of 18-60 who had data on HIV, TB and psychological distress were included (N=20208). Current HIV status, and TB status in the past year was self-reported; however, final HIV status was confirmed via dry blood spot tests. The Kessler-10 screening tool was administered to obtain information on psychological distress using the recommended cut-off score of >16 to indicate the presence of psychological distress and ≤16 to indicate the absence thereof. Descriptive statistics were used to report weighted socio-demographic-, psychological distress, and HIV and TB- characteristics of the sample. Descriptive statistics were also used to report the point prevalence of psychological distress, HIV and HIV/TB comorbidity. Logistic Regression analyses were conducted to assess the associations between demographic factors, socio-economic characteristics, HIV, TB, and psychological distress. Demographic and socioeconomic factors which were significantly associated with psychological distress in univariate analyses were included in subsequent adjusted multilevel logistic regressions to assess the association between HIV, TB, and psychological distress. The association between psychological distress and adherence was assessed among a subsample of participants with HIV using a logistical regression analysis, adjusting for significantly associated demographic and socio-economic factors. All analyses were adjusted for clustering at the small area layer to account for sampling design. Results: The prevalence of psychological distress in this sample was 33.7% (n=6479). A total of 22.2% (n=4851) were HIV positive, 0,08% (n=140) had been diagnosed with TB in the past year and 0,04% (n=84) had co-morbid HIV/TB. Age, race, gender, marital status and education were found to be associated with psychological distress. After controlling for these variables, participants living with HIV were 1.13 times as likely (95%CI=1.01-1.27) to suffer from psychological distress compared to people who did not have HIV, while participants with comorbid TB and HIV were 2.31 times as likely (95%CI=1.16-4.60) to have psychological distress. No association between psychological distress and medication adherence was found (OR=0.75, 95%CI=0.39-1.43). Conclusion: Unemployed black women who are divorced, separated, or widowed, and who have no education are most likely to suffer from psychological distress. Having a positive HIV status is associated with a greater likelihood of being psychologically distressed, which is concerning given the high prevalence of people living with HIV in South Africa. When people living with HIV also develop TB disease, their likelihood of suffering from psychological distress considerably increases compared to people who are not living with HIV. Current mental health services are grossly inadequate to meet the mental health needs of this particularly vulnerable group of public healthcare patients. Integration of mental healthcare in the public health setting is integral in addressing South Africa's mental health needs.